PELATIHAN PENINGKATAN SOFT SKILLS PENGGUNAAN MENDELEY PADA MAHASISWA PRODI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS CENDERAWASIH SEBAGAI PENDUKUNG PENYUSUNAN TUGAS AKHIR - Nurbaya Nurbaya (Fakultas Pertanian, 2023)
Mendeley is software that can help write citations and bibliography on scientific papers, with management and academic social networks to make it easier to arrange online research publications and find the most recent publication updates. It is important for students to be given training in using the Mendeley application. There are still many students, especially students who are entering their final year, who have not been able to maximize the features of the Mendeley software. The training was attended by 41 semester VI students of the Biology Education Study Program, the PMIPA FKIP UNCEN Department. The activity was carried out through several stages, namely: presentation of the introduction of Mendeley Software, installation of Mendeley Software on student software (laptops), application of Mendeley Software in Microsoft Word for citations in the preparation of the final project and evaluation on project activity. This service activity succeeded in providing an understanding of writing references/citations (Soft Skills) to semester VI students of the Biology Study Program in working on their final assignment in the form of a thesis. It is hoped that in the future, this training can be developed to the point where students can produce scientific papers that are published in international and national accredited journals.